Public governance and third sector actors in Kano, State, Nigeria: exploring engagement experiences in public policymaking - Ali, Abubakar (2020)
Public governance in Nigeria is widely perceived as dysfunctional. To address the problem, this qualitative research explored the engagement experiences of actors in public governance and the Third Sector in public policymaking situations in the most populous state in the country, Kano, in the last two decades. Using an interpretivist approach, the study focused on the experiences of elected and non-elected policy officials in the executive branch who engaged with Third Sector actors in the policymaking process. The conceptual framework that guided the study was anchored on triangulating 'heuristic' theories of network power and constructive conflict theory. The primary research design consisted of in-depth open-ended individual interviews and observations of 11 government and third sector policy executives over a period of three months in policymaking settings. The interviews were conducted in three consecutive cycles for each participant, who then 'member checked' the field reports for accuracy. All this was supplemented by relevant document sources. Finally, all interviews were transcribed, coded, and analysed by the author with the aid of NVivo 8 software. Four themes were generated from this process: engagement experience, perception of implications, changing role experience, and effective sustainability. The major finding of the research was that alhough an overwhelming number of participants favoured engagement based on pursuit of socio-centric interests in principle, actual ego-centric conduct belied those principles; while a few of the same participants had suggested that such ego-centric interests might, in the long run, impose costs that will outweigh whatever existing benefits engagement offers, especially where foreign third sector actors are concerned. The research will have implications for policy officials in government and the Third Sector who are interested in adopting an alternative mode of engagement for a more effective delivery of public services. The research concludes that social harmony, community ownership and quality service delivery outcomes are prerequisites for effective sustainability of public governance and third sector engagement.